Standardization of production technology for hybrid coloured capsicum (Capsicum annuum var grossum) based on yield and economic benefit under different protected structures in plains of India - SINGH, AWANI KUMAR; DHAR, SHRI; PERINBAN, SELLAM; SINGH, VEERPAL; KUMAR, MUKUL; KUMAR, ANJANI (The Indian Journal of Agricultural Sciences, 2016)
The present experiment was conducted to evaluate the yield and economic gain in cultivation of coloured capsicum (Capsicum annuum var grossum (L.) Sendt) hybrids in different protected structures. Six hybrids of coloured capsicum, i.e. Indra, Natasha, Bomby in red coloured group and Orobelle, Swarna, Kanchan in yellow coloured group were tried in 3 different types of protected structures compared to open field (OF) conditions. It was found that protected technology significantly enhanced crop duration (300) days in fan-pad cum force ventilated polyhouse (FFVP), 265 days in naturally ventilated polyhouse (NVP),250 days in insect proof net house (IPNH) as compared to 200 days in open fields. FFVP technology registered maximum fruit weight and yield (1.98 kg/plant, 11.83 kg/m2) followed by NVP(1.75 kg/plant, 10.42 kg/m2), IPNH(1.11kg/plant, 6.68 kg/m2) and OF (0.33 kg/plant, 1.98 kg/m2), respectively. Economic analysis of different protected structures exhibited considerably higher net returns of Rupees 247.33/m2 in FFVP, Rupees 309.67/m2 in NVP,Â Rupees 86.43/m2 in IPNH andÂ Rupees 14.75/m2 in OF condition. The benefit cost ratio was calculated as 1.73in FFVP, 2.47 in NVP, 1.48 in IPNH while the lowest value of 1.32 in OF condition. Disease incidence cum mortality of plant (2.43%) was minimum in all capsicum varieties grown under FFVP, while it was higher in NVP (6.52%) followed by IPNH (9.75%) with maximum in OF (43.65%). Whereas blossom end rot of fruits was minimum in FFVP (2.98%) followed by OF (3.28%). It is evident from the results that protected structures enhanced the production of coloured capsicum as compared to open field condition particularly during off-season in plains. Further, among different hybrid varieties evaluated, Indra in red group and Orobelle in yellow group are found more suitable for growing in these conditions while Bomby and Swarna were also performed at par under protected structure.